Research Analysis of Urdu Films Derived from Literary Novels - Subhani, Mamuna; Abbas, Waseem; Bukhari, Khurram (sourcecoder, 2022)
Literature is a name to live a life. The film is the most effective medium to depict life. No film could be successful without a good story. It gives life to the words. It tends to affect, mould, and even change people's way of life. Noval-based films always attracted people’s attention more than novels. Films like naila, Saiqa, Khak aur khon, Devdas, Gharnata, Umrao jan Ada, and Mothi Bhar Chaawal left an indelible impression on the hearts and minds of the people. Films produce better effects of horror and romance crime and repentance, love, and hatred due to audio-video effects. So, it is the most impressive source to create impact and the modern instruments have amplified its importance.